Intelligent reflecting surface aided secure MIMO wireless communication - Gao, Hongyuan; Zhao, Lishuai; Guo, Lantu; Du, Yanan; Di, Yanqi (Wireless networks, 2025)
Intelligent reflecting surface (IRS) holds tremendous potential as an efficient solution for achieving a dynamically reconfigurable wireless communication environment in a cost-efficient manner. This work explores the utilization of IRS to facilitate secure information transmission. We propose a double-IRS aided secure multiple-input multiple-output communication system model and derive the expression of the secrecy rate of this system. The introduction of eavesdropper and the coupled reflection matrices pose a significant challenge towards efficiently enhancing the secrecy rate through the joint optimization of the reflection matrices of IRSs and transmission gain matrix of the base station. To solve this problem, we propose the quantum dwarf mongoose optimization algorithm, which offers superior performance compared to the comparison algorithms. Furthermore, we compare the performance achieved by the single-IRS aided scheme with the double-IRS aided scheme and the scheme without IRS. Simulation results demonstrate that the incorporation of IRS results in a substantial enhancement of the secrecy rate due to the power amplification at the legitimate receiver and the interference suppression at the eavesdropper.